ISSUES OF FUNCTIONAL-SEMANTIC STUDY OF PAREMIOLOGICAL UNITS USED IN JOURNALISTIC TEXTS (ON THE EXAMPLE OF POLITICAL NEWSPAPERS) - Ahmadaliyeva Lutfiya Munavvarjon qizi (Modern American Journals, 2025)
This article investigates the functional and semantic aspects of paremiological units—proverbs and sayings—used in journalistic texts, focusing on political newspapers. It explores how these expressions are employed to influence readers, construct ideological stances, and enrich the linguistic style of the press. The study highlights the socio-pragmatic and rhetorical roles of paremiological units in shaping public discourse, revealing their adaptability and contextual sensitivity. The analysis is based on political texts and uncovers several issues, including cultural interpretation and semantic ambiguity.
Keywords: Paremiological units, proverbs, journalism, political discourse, functional-semantic analysis, linguistic strategy.